M Model RGB, CV, Indeks R, Indeks G, Indeks B, HSI Dan Metode Wavelet Daubechies Untuk Identifikasi Jenis Daging Sapi Untuk Mendapatkan Kualitas Daging Terbaik - Kiswanto Kiswanto; fitriyanti fitriyanti; Benny Wijaya (LPPM Universitas Mercu Buana Yogyakarta, 2020)
This image identification application can adjust to the current needs of the community in choosing the type of beef. Unfortunately, this development has not been used optimally to choose the type of beef. This is because the quality of beef is not good enough. This paper proposes a solution by calculating the values of R, G and B on each image of the flesh, then normalizing the process to get the index value R, index G and index B and the conversion process from the RGB model to the HSI model to obtain the value of Hue, Saturation and Intensity. The purpose of this study is to provide the best quality beef. This research uses RGB, CV, R Index, G Index, B Index, HIS wavelet daubechies method. This research contributes to the provision of beef-sorting services.